Analysis of the Influence of Profitability, Growth Opportunity, Liquidity, and Firm Size on Capital Structure of Pt Nippon Indosari Corporindo (Tbk) for the Years 2014-2022 - Siti Rosyafah; Fitriyah Kusuma Devi; Dhuihitta Mahardhika Lakshita (PT FORMOSA CENDEKIA GLOBAL, 2023)
The capital structure, the ratio of total debt to total assets, significantly impacts a company's financial strength. This study on PT Nippon Indosari Corporindo (Tbk) reveals important insights. Firstly, firm size, growth opportunities, liquidity, and profitability collectively influence the company's capital structure. Secondly, these factors partially impact the capital structure. Lastly, firm size, growth opportunities, liquidity, and profitability strongly shape PT Nippon Indosari Corporindo (Tbk)'s capital structure. Companies should carefully consider these factors when determining their capital structure to enhance financial stability and shareholder well-being.